Reflective Thinking Skills of Academic Administrators in Higher Education - Kasalak, Gamze; Dağyar, Miray; Özcan, Mehmet; Yeşilyurt, Etem (Frontiers in Psychology, 2022)
The aim of this study is to determine the reflective thinking skills and reflective implementations of academic administrators in higher education and to reveal the importance of reflective thinking for higher education. The research was carried out in a holistic single case design as a case study which is known as one of the qualitative research methods. The study group of the research consists of 12 faculty members who carry out administrative duties (dean and assistant dean) in ten different faculties of a public university. The data collected through a semi-structured individual interview form were analyzed by content analysis technique. According to the results obtained from the research, it has been determined that academic administrators acquire their administerial skills mostly based on their experiences, their own competences, and their tendencies to evaluate their actions individually are high, and they also consider internal and external evaluations. Reflective thinking areas related to faculty management and individual development of academic administrators were also determined, and it was concluded that they questioned faculty management mostly in terms of education and student services, and their individual development in terms of problem solving and communication skills. In addition, in the study, the characteristics of reflective academic administrators and the contributions of reflective thinking were determined based on the views of academic administrators. Finally, metaphors describing the reflective-thinking academic administrator were included, and it was found that academic administrators have a difficult job based on their management duties, they should approach everyone equally and be in the role of administrators, and that the administerial task is temporary.